Analisis Beban Kerja Fisiologis sebagai Dasar Penentuan Waktu Istirahat untuk Mengurangi Kelelahan Kerja - Wahyu Hidayat; Trismi Ristyowati; Gunawan Madyono Putro (OPSI, 2020)
510 minutes of work time a day with a break of 30 minutes is felt by employees of PT. Yogya Indo Global is too heavy. This company, which is engaged in wood processing, has 4 work stations, namely the Plenner process station, the Jointer process, Telthing and cutting parts. To reduce the physical workload in this study will be determined the length of rest time using the Indirect Assessment Method with categories of physical (physiological) workload, pulse (beats / minutes), classification% CVL (Cardiovasculair Load), calculating energy consumption, and calculate the need for rest. The study was conducted at rest at 09.30 and at 15.00 WIB. Pulse measurements are carried out using the 10 Pulse Method which then affects the amount of energy consumption. Based on the research results, it is known that at the Plenner machine work station, the Jointer and Telthing machines are in the classification of% CVL, the workload is due to the level of 30% -60%. Based on the results of the calculations, the work station for the Plenner, Jointer, Telthing and cutting process needs to be added by each time by 10 minutes, 5 minutes, 13 minutes and 10 minutes at 09.30 and the addition of 28 minutes, 25 minutes, 35 minutes and 15 at 3:00 p.m..